You are on page 1of 1

y 3 + y 2 − 4y + 1 = 0

1
3
13
65
x3 − x +
=0
3
27
13
65
p = − ,q =
3
27
s
r 
q
q 2  p 3
3
u= − +
+
2
2
3

−1 + 3i
ω=
2
1
−p
y2 = − + u +
3
3u
−p
1
y3 = − + ωu +
3
3ωu
1
−p
y1 = − + ω 2 u +
3
3ω 2 u 
  

q

1
2
2 cos
=
y1 + y1 − 4y3
13
2    

q
10π
1
2 cos
=
y1 − y12 − 4y3
13
2 
  

q

1
2 cos
=
y2 + y22 − 4y1
13
2  

 

q
1

2
=
y2 − y2 − 4y1
2 cos
13
2   


q
1

2
=
y3 + y3 − 4y2
2 cos
13
2    

q
12π
1
2 cos
=
y3 − y32 − 4y2
13
2
y =x−

y 3 + y 2 − 4y + 1 = 0
y = x − 31
65
x3 − 13
3 x + 27 = 0
13
p = − 3 , q = 65
27
q
p q
q
3
u = − 2 + ( 2 )2 + ( p3 )3

ω = −1+2 3i
y2 = − 13 + u + −p
3u
−p
y3 = − 13 + ωu + 3ωu
−p
y1 = − 13 + ω 2 u + 3ω
2u
p

1
2 cos( 13 ) = 2 (y1 + y12 − 4y3 )
p
1
2
2 cos( 10π
13 ) = 2 (y1 −p y1 − 4y3 )

1
2
2 cos( 13 ) = 2 (y2 + y2 − 4y1 )
p
1
2
2 cos( 6π
13 ) = 2 (y2 − py2 − 4y1 )

1
2 cos( 13 ) = 2 (y3 + y32 − 4y2 )
p
1
2 cos( 12π
)
=
(y

y32 − 4y2 )
3
13
2
1